Determination of the horizontal parameters of landscaping elements by means of the UAV- survey materials - Bidolakh, D. I. (Forestry and Forest Melioration, 2020)
Introduction Green areas play an important role in creating a safe and comfortable living space. Thus, it is necessary to take regular measures to protect them and organise their sustainable use and renewal. For these purposes it is important to have relevant data about the state of objects. In this situation, increasing the efficiency of the methods applied when obtaining data on landscape design parameters is impossible without the use of up-to-date technologies, namely UAV-s, GIS and others. Materials and Methods The research object is a method used to determine horizontal dimensions of landscaping elements based on the UAV-survey materials. The subject of the study was the possibility of improving the measuring of the horizontal parameters of lamdscaping objects for park design by means of modern methods. The possibility to use the results of the survey of the territory with green objects with UAV DJI Phantom 4 to determine horizontal parameters has been developed. It is established that this approach allows improving a quality, accuracy and time input of determining the length of the elements of objects in accordance with the actual cartographic material processed in the GIS-environment. The proposed method was tested in park landscapes of Berezhany, Ternopil Region, by comparing the results obtained by this approach and by the traditional measurement method. Results The deciphering of the remote sensing materials revealed a better detail of the display of the road network, contours of buildings, locations of trees and small architectural forms on the orthophotoplan, as compared with the free satellite images. When doing measurements by GIS-tools, it was also noted that the UAV-survey materials are more informative and it is more simple to determine boundaries of the elements fixed in them. The analysis of the obtained data testifies a higher results accuracy provided by the UAV-survey, as compared with free space pictures from the Google Earth platform. Considering this matter, we cannot ignore the fact that orographic factors also influence the accuracy of determining horizontal parameters of the landscaping elements. At slope angles more than 3 degrees, the effect of this parameter on the reduction of line lengths on the planned cartographic materials must be taken into account. The DEM or three-dimensional spatial planning using can help to automatically calculate the actual length of the lines in GIS, which greatly simplifies the measurement work on remote sensing materials and increases their accuracy. Conclusions It was revealed that the proposed method allows obtaining high-precision results by automating the measurement process and compiling the balance of the territory. This approach allows us to determine horizontal parameters of landscaping elements using software with the minimization of labour-intensive field work as well as it improves the accuracy compared to free remote sensing materials. It can be used in park management, in inventory the greenery, when developing landscaping projects and for research purposes. 2 Figs., 1 Table, 20 Refs. Key words: greenery elements length measurement, unmanned aerial vehicle, orthophotoplane, GIS.